2016
DOI: 10.1136/emermed-2016-206012
|View full text |Cite
|
Sign up to set email alerts
|

Obstacle course runs: review of acquired injuries and illnesses at a series of Canadian events (RACE)

Abstract: We found that 1.2% of race participants presented to onsite medical services. The majority of complaints were minor and musculoskeletal in nature. Only 2% of those treated were transferred to hospital through EMS. This is consistent with other types of mass gathering events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
3
1
0
1
Order By: Relevance
“…These results are congruent with previously reported results internationally, which demonstrate rates of less than 5.0% (0.4%-3.74%), regardless of event specifics or country of origin. 1 , 5 , 9 , 10 , 15 , 16 The EMS transport rate of 1.0% found in this study also aligns with currently published findings, which have demonstrated that less than 4.5% (0.13%-4.2%) of injures require an EMS transfer off site. 1 , 5 , 10 , 15 , 16 In summary, these findings, in collaboration with the previous studies cited, may indicate a stable trend in injury rates across the sport; up to 5.0% of participants will suffer an injury during OCR events, and less than 4.5% of all sustained injuries will require ambulance transport to an ED.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are congruent with previously reported results internationally, which demonstrate rates of less than 5.0% (0.4%-3.74%), regardless of event specifics or country of origin. 1 , 5 , 9 , 10 , 15 , 16 The EMS transport rate of 1.0% found in this study also aligns with currently published findings, which have demonstrated that less than 4.5% (0.13%-4.2%) of injures require an EMS transfer off site. 1 , 5 , 10 , 15 , 16 In summary, these findings, in collaboration with the previous studies cited, may indicate a stable trend in injury rates across the sport; up to 5.0% of participants will suffer an injury during OCR events, and less than 4.5% of all sustained injuries will require ambulance transport to an ED.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of these studies have shown that despite event specifics, difficulty, distance, location, terrain, or environmental factors, the rate of injury has consistently been between 0.40% and 3.74%. 1 , 5 , 9 , 10 , 15 , 16 Similar rates were found for EMS transport, consisting of 0.13% to 4.2% of all injuries treated. 1 , 5 , 10 , 15 , 16 There is currently no consensus as to what the upper limit of injuries or hospital transfers is.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…Az akadályfutás során a résztvevőknek változatos terepen kell futniuk, és akadályokat kell teljesíteniük. Az akadályok nem teljesítése büntetést vagy kizárást vonhat maga után (Hawley et al 2017).…”
Section: áLlóképességi Sportversenyek éS Fajtáiunclassified